2023
DOI: 10.33494/nzjfs532023x178x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of tending on attributes of radiata pine trees and stands in New Zealand – a review

Euan G. Mason

Abstract: Background: Radiata pine (Pinus radiata D.Don) has been grown in New Zealand’s plantations for more than a century, and silviculturists began by employing Eurocentric ideas about how to manage forest stands. Research and development gradually led to an entirely new approach to silviculture, where volume production was sacrificed to promote value, and high investments in individual trees led to very low stand stockings by international standards. Methods: The development of pruning and thinning technology was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Mason & Cullen (1986) found that soil ripping, with or without soil mounding, reduced toppling incidence. Trees planted on ripped sites had better root form and vertical root growth than trees growing on unripped sites (Mason et al 1988). Similarly, Somerville (1979) found that the vertical distribution and form of roots of 11.5-year-old radiata pine trees were improved by ripping-even though the amount of below-ground biomass remained relatively unaffected by this treatment.…”
Section: New Zealand Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Mason & Cullen (1986) found that soil ripping, with or without soil mounding, reduced toppling incidence. Trees planted on ripped sites had better root form and vertical root growth than trees growing on unripped sites (Mason et al 1988). Similarly, Somerville (1979) found that the vertical distribution and form of roots of 11.5-year-old radiata pine trees were improved by ripping-even though the amount of below-ground biomass remained relatively unaffected by this treatment.…”
Section: New Zealand Studiesmentioning
confidence: 95%
“…New Zealand studies have ranged from descriptive, including photographing or drawing of root systems (e.g., Watson & O'Loughlin 1985, Ross et al 2004 ), to the development of more systematic assessments and indices (e.g., Somerville 1979;Balneaves & de la Mare 1989). Reported New Zealand root morphology indices (Balneaves & de la Mare 1989;Mason 1985) are generally subjective and have been used to compare tree performance following different plant establishment treatments such as soil ripping. They tend to focus on an appraisal of taproot distortion, lateral root arrangement, and root tangle.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With alternative tree species, the most relevant costs are opportunity costs in profitability relative to that of growing radiata pine. Because of lower productivity, or need for longer rotations, or much greater sensitivity to site variation, and often problems of utilisation and marketing their wood, alternative species are typically far less profitable to grow than radiata pine (Maclaren 2005 3 ). Site sensitivity can effectively reduce a species' wide use, often making them more suited to small growers of speciality woods.…”
Section: Risk-reward Relationships For Radiata Pinementioning
confidence: 99%
“… 3 Maclaren 2005 looks at optimum situation, but this is less common with alternative species than radiata pine.…”
mentioning
confidence: 99%